2019
DOI: 10.1016/j.clgc.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prediction Tool for Exclusive Locoregional Recurrence After Radical Cystectomy in Patients With Muscle-Invasive Bladder Cancer

Abstract: We analyzed prognostic factors and developed a prediction tool for exclusive locoregional (pelvic) recurrences after radical cystectomy for bladder cancer. We identified a subgroup of patients with the highest risk who might be best suited for clinical studies. Background: Limited information is available about the pattern of relapse after perioperative chemotherapy with radical cystectomy (RC) vs. RC alone in muscle-invasive bladder cancer. Patients and Methods: Data from 1082 patients of the Retrospective In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The prognosis of MIBC remains largely unchanged in the past several decades, partly because of insufficient therapeutic options (30). Recent studies indicated that MIBC can be classified into multiple molecular subtypes, suggesting patients with MIBC may require personalized therapeutic strategies based on their molecular signatures (31).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of MIBC remains largely unchanged in the past several decades, partly because of insufficient therapeutic options (30). Recent studies indicated that MIBC can be classified into multiple molecular subtypes, suggesting patients with MIBC may require personalized therapeutic strategies based on their molecular signatures (31).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that of Europe, its global SIR is 4.3 for female and 20.2 for male [ 29 , 30 ]. Of all European countries, the highest SIR is in Greece with 4.5 in women and 40.4 in men, while the lowest is in Austria with 3.0 in women and 9.9 in men [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although their results corroborate the use of adjuvant RT for improving locoregional control and disease-free survival or OS, the findings are not definitive due to their small sample sizes, retrospective study design, and heterogeneities. 9 19 20 Two historical prospective randomized trials from Egypt have demonstrated that postoperative RT improved locoregional control and disease-free survival; the 5-year locoregional control rate was 93% in the postoperative RT group and 50% in the observational group ( p < 0.05). 9 19 However, this study was limited by the fact that only 20% of the patients had urothelial cell carcinoma, and that an old RT technique (2D RT) was used.…”
Section: Discussionmentioning
confidence: 99%